Smallholder irrigation technology diffusion in Mali: Insights from stakeholder mapping - Houeto, Dede Aduayom; Diamoutene, Abdoul K.; Diop, Loty; Ringler, Claudia (International Food Policy Research Institute, 2022)
Small-scale irrigation has significant potential to increase crop productivity in Mali, in particular given growing climate change impacts on the country and region. While large-scale development is substantial, small, private irrigation remains limited, affecting food and particularly nutrition security as small-scale technologies are more likely to be used for high-value vegetable crops. To better understand the challenges and opportunities in the diffusion of small-scale irrigation technologies, two workshops were organized in 2021 at the national and regional levels, respectively, to consider national and local factors supporting the diffusion of small-scale irrigation technologies. Key constraints identified were a lack of linkages between intermediary organizations in the small-scale irrigation diffusion process, such as commodity associations, financial institutions and technology vendors with government agencies in charge of irrigation, limiting the sharing of consistent and effective information across entities; the lack of a clear policy framework and long-term guidance for private individual irrigation; an associated lack of targeted technology development including limited adaptation to different local contexts, missing financial products linked to irrigation technology, and inadequate capacity building of farmers through extension services and demonstration sites. Workshop participants suggested a dedicated platform for more effective information exchange across the key actors identified in the events, improved capacity building on private irrigation, and a supportive policy and financial environment to ensure growth and sustainability of small-scale irrigation development in the country.